Effects of Pretreatment and Drying Methods on the Quality of Sorghum Flour and Its Application in Pancake Production - Wongtom, Rungtip (Journal of Food Technology, Siam University, 2019)
The objective of this research was to investigate pretreatment and drying methods and their effects on sorghum flour qualities and application in pancake. The experiment was laid out using a 3x2 factorial completely randomized design with 3 preparation methods (sorghum soaking in water for 15 minutes, steaming for 15 minutes and boiling for 4 minutes) and 2 drying methods (tray drying and freeze drying). The results show that the preparation methods of sorghum affected sorghum flour on moisture, water activity, peak viscosity, breakdown, peak time, pasting temperature and color value (L*, a*, b*). The preparation methods affected on structure of sorghum flour were analyzed using Scanning Electron Microscope (SEM) at 3000X magnification. The morphology of sorghum flour pretreated with moisture heat was bigger than that of the control. Pancakes made from all pretreated sorghum flours followed by freeze drying demonstrated a higher sensory acceptance score in terms of texture than that of the others (p<0.05).